Proceedings of the 2018 International Conference on Islamic Economics and Business (ICONIES 2018) 2019
DOI: 10.2991/iconies-18.2019.66
|View full text |Cite
|
Sign up to set email alerts
|

Does Managerial Ability and Corporate Governance Mitigate Tax Avoidance Activities When Environmental Uncertainty is Considered?

Abstract: This study aims to examine the effect of environmental uncertainty on tax avoidance with a managerial ability and corporate governance as a moderating role in it. The sample used in this study is a company listed on the Indonesia Stock Exchange (IDX) period 2014-2016. Abnormal Book-Tax Difference (ABTD) considered as an appropriate measurement of tax avoidance in this study because considering of misleading created from management discretion as another cause of tax avoidance in addition to the differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The results of this test support the results of research conducted by Ratu and Siregar, (2019), Seviana and Kristanto, (2020), and research by Syarendra and Kristanto, (2020) which states that environmental uncertainty has a significant positive effect on tax avoidance.…”
Section: Effect Of Environmental Uncertainty On Tax Avoidancesupporting
confidence: 85%
See 1 more Smart Citation
“…The results of this test support the results of research conducted by Ratu and Siregar, (2019), Seviana and Kristanto, (2020), and research by Syarendra and Kristanto, (2020) which states that environmental uncertainty has a significant positive effect on tax avoidance.…”
Section: Effect Of Environmental Uncertainty On Tax Avoidancesupporting
confidence: 85%
“…In addition, regarding the independent variable environmental uncertainty on tax avoidance, there have been previous studies conducted by Ratu and Siregar, (2019), Seviana and Kristanto, (2020), Syarendra and Kristanto, (2020) and Arieftiara, et al, (2020) which states the results of his research that environmental uncertainty has affect tax avoidance. Meanwhile, research conducted by Huang, et al, (2017) states that the results of the study show that environmental uncertainty has no effect on tax avoidance.…”
Section: Introductionmentioning
confidence: 96%
“…A volatile environmental causes firms to be more careful in planning, including tax planning because taxes represent a significant expense for the firms and reduce shareholders' wealth. Ratu & Siregar (2018) found that firms that face high environmental uncertainty will increase tax avoidance activities. Firms with high environmental uncertainty will face a more risky situation so that firms will try to display the image of a low-risk by managing firms' cash flow by lowering firms' costs.…”
Section: Introductionmentioning
confidence: 99%
“…It means that high-ability managers can employ an optimum level of tax avoidance strategies. The papers such as Park et al (2016), Baik et al (2018), Gul et al (2018), Khurana et al (2018), Ratu and Siregar (2019), Lee and Yoon (2020), Salehi et al (2020b), also find an ameliorating role for managerial ability in mitigating negative factors on firm value…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, managerial ability does not affect the association between product market competition and investment decisions. Ratu and Siregar (2019) show significant positive evidence of the effect of environmental uncertainty on tax avoidance. Gul et al (2018) showed a significant association between firm acquisition decisions and corporate tax avoidance.…”
Section: Theoretical Frameworkmentioning
confidence: 94%